β-Defensins: Farming the Microbiome for Homeostasis and Health - Meade, Kieran G.; O'Farrelly, Cliona (Frontiers in Immunology, 2019)
Physiological sterility is fast becoming an obsolete concept in the light of emerging evidence documenting the presence of a resident foetal microbial population thought to be transferred from the intestine of the expectant mother. A commensal microbiome has also recently been identified in healthy breast milk as well as in semen, adding a whole new dimension to our deliberations on host-microbe interactions. Growing too is our appreciation of the complexity of microfloral management required in eukaryotes to maintain homeostasis. Transitioning from non-selective, antibiotic-mediated treatments for clearance of microbes is a completely new paradigm, particularly in veterinary medicine, and a balanced commensal population is now regarded as key to optimal protection against disease. Central to this management system is the expression of evolutionarily conserved host defence peptides (HDPs), known as β-defensins. These multifunctional cationic peptides manage the cross-talk between host and microbes to maintain a healthy yet dynamic equilibrium across mucosal systems, thereby protecting oral, respiratory, reproductive and enteric tissues from pathogen-associated inflammation and disease. Expansions in the number of genes encoding these natural antibiotics have been described in the genomes of some species, the functional significance of which has only recently being appreciated. β-defensin expression has been documented pre-birth and disruptions in their regulation may play a role in maladaptive neonatal immune programming, thereby contributing to subsequent disease susceptibility. Here we review the body of recent evidence supporting a critical role for β-defensins as farmers of this pervasive and complex prokaryotic ecosystem. We also share some new perspectives on the role of β-defensins as sensors of homeostasis and the immunity vanguard particularly at sites of immunological privilege where inflammation is attentuated.